Supporting Components for the Success of Gifted Students in Quran Memorization - Mutathahirin Mutathahirin; Azhar Jaafar; Rashidi Abbas; Nuha Sufina Binti Saidi (Journal of Theory and Research Memorization Quran, 2026)
This study aims to discover three supporting components that contribute to the success of gifted students in Quran memorization, namely parental support, teacher support, and peer support. A qualitative case study approach was employed, with data collected from twenty purposively selected gifted students actively engaged in Quranic memorization programs. In-depth interviews were conducted, and thematic analysis was performed using NVivo 12 software to identify recurring themes and patterns. The findings reveal that parental support is provided through motivation, emotional encouragement, a conducive environment, and active involvement in accompanying memorization. Teacher support is realized through systematic memorization techniques, continuous monitoring and evaluation, and motivational reinforcement. Peer support contributes through group memorization, healthy competition, and mutual moral encouragement. Overall, the success of Quran memorization among gifted students is strongly influenced by the synergy of family, school, and social environments. This study emphasizes that the integration of parental, teacher, and peer support is essential for designing systematic and comprehensive Quranic memorization programs, and the findings provide practical insights for educators and policymakers in strengthening tahfiz education as a medium for intellectual, moral, and spiritual development of gifted students.